Big data analytics : applications in business and marketing - Chaudhary, Kiran; Alam, Mansaf (Boca Raton : CRC Press, 2022)
Big Data Analytics: Digital Marketing and Decision-Making covers the advances related to marketing and business analytics. Investment marketing analytics can create value through proper allocation of resources and resource orchestration processes. The use of data analytics tools can be used to improve and speed decision-making processes. Chapters examining analytics for decision-making cover such topics as: Big data analytics for gathering business intelligence Data analytics and consumer behavior The role of big data analytics in organizational decision-making This book also looks at digital marketing and focuses on such areas as: The prediction of marketing by consumer analytics Web analytics for digital marketing Smart retailing Leveraging web analytics for optimizing digital marketing strategies Big Data Analytics: Digital Marketing and Decision-Making aims to help organizations increase their profits by making better decisions on time through the use of data analytics. It is written for students, practitioners, industry professionals, researchers, and faculty working in the field of commerce and marketing, big data analytics, and organizational decision-making.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Database Management / Data Mining; BUSINESS & ECONOMICS / E-Commerce / Internet Marketing; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Business -- Data processing; Marketing -- Data processing; Big data